Second Language Trajectories in Immigrant Children: Latent Class Growth Analysis - Larissa Maria Troesch; Loredana Torchetti; Sonja Hasler; Alexander Grob (Education Sciences, 2025)
The present study aims to investigate whether there are different second language trajectories among immigrant children and what influences these trajectories. This longitudinal study included 443 children all learning German as a second language (49.9% girls). On average, at T1, the children were 3;6; at T2, 4;9; at T3, 6;2; and at T4, 7;3 years old. Discontinuous piecewise latent class growth analysis revealed four classes: improvement to low-level proficiency, improvement to medium-level proficiency, improvement to high-level proficiency, and permanent high-level proficiency. Class membership was predicted by early childcare attendance, the duration of the parents’ residence in Switzerland, contact with German speakers, the child’s cognitive abilities, and the parental socioeconomic status.